KOMPARASI KUALITAS PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN TIPE NHT DAN TIPE STAD - Fatmawati, Ulfa; Usman, Muhammad Rizal; Satriani, Sri (JURNAL MathEdu (Mathematic Education Journal), 2023)
The purpose of this study was to examine the comparison of the quality of learning mathematics through the NHT and STAD models. This type of research is a quasi-experimental. The population in this study were all students of class VII SMP SMP Putri Yatama Mandiri in the 2021/2022 academic year and the samples in this study were taken by Saturated Sampling, namely class VIIA which was taught through the NHT model with a total of 25 students and class VIIB which was taught through the STAD model with a total of 25 students. The research design was a pretest-posttest control group design, which involved two classes that were given a pretest and a posttest. Data collection techniques are observation sheets of the implementation of learning and student activities, learning achievement tests, student response questionnaires. The results showed: 1) the average pretest score of students through the NHT model was 29.44 (very low) with a standard deviation of 6.01, 100% did not achieve individual mastery, meaning that classical mastery was not achieved, 2) the average score the average posttest of students through the NHT model is 85.20 (high) with a standard deviation of 5.35, 100% of students achieve individual mastery, meaning that classical mastery is achieved, 3) the average score of students' pretest through the STAD model is 38.08 (very low) with a standard deviation of 7.49, 100% obtained did not achieve individual completeness, meaning that classical mastery was not achieved, 4) the average posttest score of students through the STAD model was 81.6 (medium) with a standard deviation of 6.14, it was found that 23 students or 92% achieved individual mastery, meaning that classical mastery was achieved, 5) the average percentage of student response questionnaires that answered yes on NHT was 94.5% and on STAD 97%, meaning that 75% of students had fulfilled answer YES, and 6) the average gain is 0.79 on NHT and 0.70 on STAD. Thus the quality of learning mathematics through the application of the NHT model is not the same as learning mathematics through the application of the STAD model in class VII students of SMP Putri Yatama Mandiri Islamic Boarding School.